Who arrived first? Priority effects on Candida albicans and Pseudomonas aeruginosa dual biofilms - Betsy V. Arévalo-Jaimes; Joana Admella; Eduard Torrents (Communications Biology)
Abstract Historical processes in community assembly, such as species arrival order, influence interactions, causing priority effects. Candida albicans and Pseudomonas aeruginosa often co-occur in biofilm-based infections of the skin, lungs, and medical devices. Their predominantly antagonistic relationship involves complex physical and chemical interactions. However, the presence and implications of priority effects among these microorganisms remain largely unexplored. Here, we investigate the presence and impact of priority effect in dual-species biofilms using clinical isolates. By varying inoculation order, we observe significant changes in biofilm composition, structure, virulence, and antimicrobial susceptibility. The first colonizer has an advantage for surface colonization. Consecutive colonization increases biofilm virulence and negates C. albicans’ protective effect on P. aeruginosa PAET1 against meropenem treatment. Finally, we propose N-acetylcysteine as an adjuvant for treating C. albicans and P. aeruginosa interkingdom infections, working independently of priority effects.